Small Bowel Enteroscopy - A Joint Clinical Guideline from the Spanish and Portuguese Small Bowel Study Groups - Pérez-Cuadrado-Robles, Enrique (2020)
The present evidence-based guidelines are focused on the use of device-assisted enteroscopy in the management of small-bowel diseases. A panel of experts selected by the Spanish and Portuguese small bowel study groups reviewed the available evidence focusing on the main indications of this technique, its role in the management algorithm of each indication and on its diagnostic and therapeutic yields. A set of recommendations were issued accordingly.